Respuesta :
1. Isolate x in the first equation:
x = 7 – 3y
2. Substitute the value for x into the second equation:
2(7 – 3y) + 4y = 8
3. Solve for y:14 – 6y + 4y = 8
14 – 2y = 8
–2y = –6
y = 3
4. Substitute y into either original equation:
x + 3(3) = 7
x + 9 = 7
x = -2
5. Write the solution as an ordered pair:
(-2 , 3)
hope it helps
x = 7 – 3y
2. Substitute the value for x into the second equation:
2(7 – 3y) + 4y = 8
3. Solve for y:14 – 6y + 4y = 8
14 – 2y = 8
–2y = –6
y = 3
4. Substitute y into either original equation:
x + 3(3) = 7
x + 9 = 7
x = -2
5. Write the solution as an ordered pair:
(-2 , 3)
hope it helps
1) x= 7 - 3y
2) 2(7 - 3y) + 4y = 8
3) 14 - 6y + 4y =8
14 - 2y = 8
- 14 + 14 - 2y = 8 - 14
2y = 6
y = 3
4) x=7 - 3y = 7 - 3*3 =7 - 9 = -2
5) (-2, 3)
2) 2(7 - 3y) + 4y = 8
3) 14 - 6y + 4y =8
14 - 2y = 8
- 14 + 14 - 2y = 8 - 14
2y = 6
y = 3
4) x=7 - 3y = 7 - 3*3 =7 - 9 = -2
5) (-2, 3)